2007
DOI: 10.3748/wjg.v13.i20.2798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyapatite nanoparticles on the growth and p53/c-Myc protein expression of implanted hepatic VX2 tumor in rabbits by intravenous injection

Abstract: AIM:To evaluate the effect of hydroxyapatite nanoparticles (Nano HAP) by intravenous injection on the inhibition of implanted hepatic VX2 tumor growth in rabbits and cell p53/c-Myc protein expression. METHODS:60 hepatic VX2 tumor-bearing rabbits was randomly divided into five groups. Nano HAP collosol 20 mg/kg, 40 mg/kg, 5-FU solutions 20 mg/mL, mixed liquor of 5-FU solution 20 mg/mL and Nano HAP collosol 20 mg/kg were infused by vein, normal saline conducted as the control. The general state, weight, liver fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Whilst Jun et al showed that HAP nanoparticles inhibit the growth of hepatic tumour cells and have stronger anti-tumour effect, Li et al demonstrated a beneficial effect of a nanocomposite of HAP and chitosan on human gastric cancer cells [15][16]. Another advantage of HAP is that it is biocompatible as implants and provides a biological scaffold for bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst Jun et al showed that HAP nanoparticles inhibit the growth of hepatic tumour cells and have stronger anti-tumour effect, Li et al demonstrated a beneficial effect of a nanocomposite of HAP and chitosan on human gastric cancer cells [15][16]. Another advantage of HAP is that it is biocompatible as implants and provides a biological scaffold for bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…According literature data, the increase of p53 expression occurs as result cellular response to various types of cell damage. However, several experimental results evidence that the suppression of p53 expression is the mechanism to regulate of transcriptional activity too, especially the inhibition with microRNA or hydroxyapatite nanoparticles (Hu et al, 2007;Cho et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These tumors are well characterized and the method of their induction has been thoroughly studied. Finally, the VX2 molecular biology includes alterations within the function of p53 (31), which also occurs in up to 75% of pancreatic cancers (5). This suggests a degree of molecular homology between the VX2 tumors and human pancreatic tumors, further supporting this model’s utility.…”
Section: Discussionmentioning
confidence: 99%